Defining patterns in the influence exerted by the interelated biochemical corrosion on concrete building structures under the conditions of a chemical enterprise - Shkromada, Oksana; Ivchenko, Viktoriia; Chivanov, Vadym; Tsyhanenko, Liudmyla; Tsyhanenko, Hennadii; Moskalenko, Volodymir; Kyrchata, Іryna; Shersheniuk, Olena; Litsman, Yuliia (Eastern-European Journal of Enterprise Technologies, 2021)
The effect of microbial and chemical corrosion on concrete structures operated in the conditions of chemical enterprises has been established that makes it possible to reliably predict the timing of their decommissioning in order to prevent industrial disasters. Even though the construction complies with all building codes, concrete structures eventually undergo chemical and biological corrosion. The innovation proposed in this study implies investigating the depth and degree of damage to concrete at the microscopic level by the method of raster electron microscopy. In addition, the TPD-MS method has been suggested for determining the quantitative and qualitative state of the carbonate components of concrete and sulfur compounds. This study has found that in concrete samples from the titanium dioxide production plant, the amount of carbon dioxide release is twice less than in control samples at t=600 °C while the level of sulfur dioxide, on the contrary, increases. This is due to the ability of thionic bacteria to accumulate sulfate acid that destroys the cementing component in concrete. The reported results confirm the impact of products of the activity of Acidithiobacillus thiooxidans microorganisms on corrosion processes in concrete. In addition, when using the TPD-MS method, it was established in the storage room of the finished product that heating the control sample of concrete leads to a release of the significant amount of СО2 at t=580–600 °C. However, the experimental samples of concrete are almost lacking carbon compounds because the acid metabolites of microfungi interfere with its formation. Microscopic and REM studies revealed the localization of Acidithiobacillus thiooxidans and Aspergillus fumigatus in concrete. This study has established patterns related to the mechanism that forms chemical compounds in concrete and the metabolism of microorganisms